2015
DOI: 10.1128/jvi.02953-14
|View full text |Cite
|
Sign up to set email alerts
|

RNase L Targets Distinct Sites in Influenza A Virus RNAs

Abstract: Influenza

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…Given the selection for OAS isoforms and the recent implication of the OAS/RNAseL system in MDA5 activation (Luthra et al, 2011; Malathi et al, 2007), we next investigated whether this intrinsic cellular defense against IAV was responsible for amplifying the host antiviral response. Indeed, this same pathway has been suggested to be an effective antiviral activity against IAV and one of the primary targets of the NS1 protein (Cooper et al, 2015; Min and Krug, 2006). Moreover, the recent finding that MDA5 aids in exposing viral dsRNA to the host machinery would suggest that MDA5 could enhance the activity of the OAS/RNAseL system (Yao et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…Given the selection for OAS isoforms and the recent implication of the OAS/RNAseL system in MDA5 activation (Luthra et al, 2011; Malathi et al, 2007), we next investigated whether this intrinsic cellular defense against IAV was responsible for amplifying the host antiviral response. Indeed, this same pathway has been suggested to be an effective antiviral activity against IAV and one of the primary targets of the NS1 protein (Cooper et al, 2015; Min and Krug, 2006). Moreover, the recent finding that MDA5 aids in exposing viral dsRNA to the host machinery would suggest that MDA5 could enhance the activity of the OAS/RNAseL system (Yao et al, 2015).…”
Section: Resultsmentioning
confidence: 96%
“…The influenza A virus (IAV) non-structural 1 protein (NS1) contains an N-terminal RNA-binding domain which binds to and sequesters dsRNA, the activator of OAS [39][40][41]. RNase L inhibits IAV (NS1-mutant) replication by cleaving viral genomic RNA in sites encoding PB2, PB1, and PA proteins critical for viral replication [42]. In a similar mechanism, the herpes simplex virus type 1 (HSV1) US11 gene product [43] and vaccinia virus (VacV) E3L protein binds dsRNA to inhibit the innate immune response [44][45][46].…”
Section: Cellular and Viral Inhibitors Of Oas-rnase Lmentioning
confidence: 99%
“…RNase L cleaves cellular and viral RNAs within single-stranded regions after a UN dinucleotide (with a preference in the order of UU > UA ) UG > UC). Studies focused on identifying the RNA targets of RNase L have provided some insight on cellular and viral targets [18,42,84,85]. A recent microarray-based study identified certain target mRNAs regulated by RNase L activation.…”
Section: Rnase L Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been found that RNA sequence is very specific for ribonucleases (for example, RNase H) [6062]. To understand the substrate sequence specificity and site specificity, deep sequencing methods (for review see [6365]) were used to investigate the frequency and locations of ribonuclease L cleavage sites of viral RNAs [66, 67]. Site-specific studies have also been carried out, using primer extension reactions to characterize ribonuclease L specific cleavage sites in hepatitis C virus RNA [68] and DNA damage sites [69].…”
Section: Techniques For Multiplexed High Throughput Measurements mentioning
confidence: 99%